2023
DOI: 10.1186/s43556-023-00119-1
|View full text |Cite
|
Sign up to set email alerts
|

CD95/Fas ligand mRNA is toxic to cells through more than one mechanism

Abstract: CD95/Fas ligand (CD95L) induces apoptosis through protein binding to the CD95 receptor. However, CD95L mRNA also induces toxicity in the absence of CD95 through induction of DISE (Death Induced by Survival Gene Elimination), a form of cell death mediated by RNA interference (RNAi). We now report that CD95L mRNA processing generates a short (s)RNA nearly identical to shL3, a commercial CD95L-targeting shRNA that led to the discovery of DISE. Neither of the miRNA biogenesis proteins Drosha nor Dicer are required… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…We subsequently reported that CD95L is enriched in sequences that when converted to sRNAs are toxic to cells. In fact, we found that CD95L is processed into short RNAs (sRNAs) that are loaded into the RNA induced silencing complex (RISC) and kill cells through DISE [ 10 , 11 ]. Later, we determined that all these toxic sRNAs did not kill cells by acting like typical siRNAs i.e., by silencing genes through complete complementarity to a section of the mRNA, but by working in a microRNA (miRNA)-like fashion i.e.…”
mentioning
confidence: 99%
“…We subsequently reported that CD95L is enriched in sequences that when converted to sRNAs are toxic to cells. In fact, we found that CD95L is processed into short RNAs (sRNAs) that are loaded into the RNA induced silencing complex (RISC) and kill cells through DISE [ 10 , 11 ]. Later, we determined that all these toxic sRNAs did not kill cells by acting like typical siRNAs i.e., by silencing genes through complete complementarity to a section of the mRNA, but by working in a microRNA (miRNA)-like fashion i.e.…”
mentioning
confidence: 99%